The Perils of a Defective Medical Communication: Fatal Neglected Squamous Cell Carcinoma Arising in Perineal Hidradenitis Suppurativa - Pagliarello, Calogero (S. Karger AG, 2011)
Hidradenitis suppurativa (HS) is a recurrent suppurative disease characterized by inflammatory nodules, abscesses, fistulas, and scarring. We report a case of squamous cell carcinoma arising in chronic HS. In our case the asymptomatic lesion was neglected by the patient for a long time, allowing the occurrence of advanced disease before treatment was sought, which resulted in a terminal outcome. In the context of HS, a painful lump or ulcer could easily be mistaken for an inflammatory lesion, and therefore a low threshold for biopsy is warranted.